Circulating circular RNA profiles associated with celiac disease seropositivity in children with type 1 diabetes - Juan-juan Zhang; Jun-qi Wang; Xu Xu; Li-dan Zhang; Cai-ping Zhang; Wen-li Lu; Wei-qiong Gu; Zhi-ya Dong; Yuan Xiao; Zhen-wei Xia (Frontiers Media S.A., 2022)
IntroductionThe frequency of celiac disease autoantibody (CDAb) positivity in type 1 diabetes (T1D) has increased due to unclear mechanisms, including autoimmune injury. Circular ribonucleic acids (circRNAs) participate in autoimmune diseases, but the roles of circRNAs in T1D with CDAbs are currently unknown. This study aimed to determine the frequency of CDAbs in Chinese children with T1D and describe the relationship between CDAbs and circRNAs.Materials and methodsEighty patients diagnosed with T1D were screened for CDAbs and CD-predisposing genes, and circRNAs in peripheral blood mononuclear cells (PBMCs) were collected from 47 patients. The Gene Expression Omnibus (GEO) database was searched for candidate circRNAs in related studies on T1D PBMCs. Data on clinical characteristics (i.e., blood glucose control, residual islet function, and daily insulin dosage) and immunophenotypes (i.e., islet autoantibodies and immune cell subsets) were collected.ResultsIn total, 35.0% of patients were positive for CDAbs. CD-predisposing genes accounted for 52.5% of the genes, and no significant difference in frequency was found between the CDAb-positive (CDAb+) and CDAb-negative (CDAb-) groups. In addition, among the differentially expressed circRNAs from the GEO database, five highly conserved circRNAs homologous to humans and mice were screened, and only the expression of hsa_circ_0004564 in the CDAb+ group significantly decreased (CDAb+ vs. CDAb-:1.72 ± 1.92 vs. 11.12 ± 8.59, p = 6.0 × 10-6), while the expression of hsa_circ_0004564 was upregulated in the general T1D population. Moreover, its parental gene RAPH1 was significantly upregulated (CDAb+ vs. CDAb-:1.26 ± 0.99 vs. 0.61 ± 0.46, p = 0.011). Importantly, the positive correlation between hsa_circ_0004564 and CD3+ cells was validated in children with T1D after adjustments for CDAbs (p = 0.029), while there were no correlations between hsa_circ_0004564 and clinical characteristics or other immune cell subsets (i.e., CD4+ T cells, CD8+ T cells, and natural killer cells).ConclusionThis study highlights the importance of screening for CD in Chinese children with T1D, considering the high prevalence of CDAb positivity and CD-predisposing genes. The profile of candidate circRNAs in children with T1D with CDAbs was different from that in previous reports on general T1D patients from the GEO database. Moreover, hsa_circ_0004564 and its parental gene RAPH1 may be new targets for studying immune mechanisms in children with T1D and CD.